Screening and validation of lymph node metastasis risk-factor genes in papillary thyroid carcinoma - Zhang, Qiaoyue; Li, Jing; Shen, Hengyan; Bai, Xinyu; Zhang, Tao; Liu, Ping (Frontiers in Endocrinology, 2022)
Background: Although most papillary thyroid carcinoma (PTC) cases have a good prognosis, some are more aggressive, and are often accompanied by lymph node (LN) metastasis, a high recurrence rate, and poor prognosis. Distinguishing highly invasive metastatic PTC is an urgent problem that needs to be addressed clinically. We analyzed the microarray of metastasized PTC and validated it using real-time qualitative PCR (RT-qPCR) and immunohistochemistry to identify biomarkers that can be used to assess the risk of PTC metastasis. Methods: The microarray of metastasized PTC was screened using the Gene Expression Omnibus (GEO) database. The differences between cancer and normal tissues were analyzed using the GEO official tool GEO2R. Gene expression profile data (GEPIA) were used to verify the expression of differential genes in large samples and to analyze their correlation. The Kaplan–Meier-Plotter (KM-plotter) database was used for the analysis of genes potentially related to survival. RT-qPCR was used to check on the expression of risk factor genes in pathological sections from PTC patients with clinical LN metastasis. Immunohistochemistry was used to verify the expression of core risk-associated genes. Results: Fourteen PTC metastasis-associated genes were identified. In metastasized PTC, CLDN1, LRP4, LRRK2, and TENM1 were highly expressed, whereas DIO1, DPP6, HGD, IPCEF1, MT1F, SLC26A4, SLC26A7, SPX, TFF3, and TPO were expressed at low levels, compared to their expression in normal tissues. DIO1, HGD, SLC26A4, and TPO were found to be the core risk genes in the PTC transfer risk set. Results based on clinical samples showed that the expression differences for metastasis risk-associated genes were consistent with the bioinformatics analysis results. Conclusions: Fourteen differentially expressed genes (CLDN1, LRP4, LRRK2, TENM1, DIO1, DPP6, HGD, IPCEF1, MT1F, SLC26A4, SLC26A7, SPX, TFF3, TPO) are associated with an increased risk of PTC metastasis, and DIO1, HGD, SLC26A4, and TPO are the key risk-associated genes in this set and might affect the occurrence and development of PTC through iodine metabolism. These genes could provide a reference for clinical metastatic PTC risk evaluation and treatment.